Decalcified choroidal osteoma found in the retina - Yoshikawa T (Dove Medical Press, 2012)
Tadanobu Yoshikawa, Kanji TakahashiDepartment of Ophthalmology, Kansai Medical University, Hirakata Hospital, Osaka, JapanAbstract: Choroidal osteoma is a benign tumor of the choroid. Herein, we report a rare case of decalcified choroidal osteoma found in the retina. A 27-year-old woman presented with visual loss. Her best-corrected visual acuity was 20/50 OS. Ophthalmoscopy of the left eye revealed a yellow-white calcified region accompanied by a decalcified region of four disc diameters in size. After 6 years, spectral-domain optical coherence tomography showed a tumor projected strongly upwards from the choroid and partially through the retina with serous retinal detachment, with both a lamellar appearance and mound-like area. The calcified region became more contractive than was observed on the first visit. Conversely, the decalcified region was wider than was observed on the first visit. Her best-corrected visual acuity was 20/400 OS. Choroidal osteoma was worsened by progression of decalcification. The decalcified choroidal osteoma resulted in poor visual acuity, and projected strongly upward from the choroid and into the retina.Keywords: osteoma, decalcification, choroidal osteoma